Performing test systems and test items - Caroli, Sergio (Henry Stewart Talks, 2013)
Animal rooms, Biological test systems, Characterization of test systems, Choice of test systems, Definition of test item, Definition of test system, Integrity of Good Laboratory Practice studies, Isolation of biological test systems, Performing of Good Laboratory Practice studies, Physical-chemical test systems, Proper characterization of the test item in cooperation with the sponsor, Proper identification of the test item in cooperation with the sponsor, Quarantine of biological test systems, Separation of biological test systems, Storage facilitie